Dynamic Model on Palm Oil Production Capacity Using Variable CPO Stock for Biofuel Production - Setiawan, Arrie Tjahyo; Dalimi, Rinaldy (International Journal of Electrical, Computer, and Biomedical Engineering, 2024)
The role of biofuel for running diesel power plants is therefore indispensable for compensating various renewable plants with fluctuating output, maintaining stability to the overall power system. For expanding biofuel production, keeping the rate of investment in CPO mills is critical, as it is often driven by CPO business profit. The seasonal nature of palm-oil plantation harvest directly influences CPO production behaviour. This research investigates system dynamics model simulation for CPO production system, indicated by the feedback loop from market demand, hence influencing the daily (or monthly) CPO production to provide revenue stream to the business. Subsequently, it influences the rate of investment for increasing production capacity, forming the dynamic hypothesis for the system. The model was developed using endogenous variables, while trying to reduce the number of external inputs required to run the simulation. By substituting the price variable with the level of CPO stock at the national level, less uncertainties would affect the system such as price instability situation. Feedback signal from the level of CPO stock was utilized to control the simulated amount of CPO production, as well as the rate of re-investment for expanding the country’s production capacity. Model simulation results was able to reproduce the system behaviour for capacity increase, to meet CPO market demand. The model structure could be further replicated for efficiently developing the dynamic model for basic commodity production, where the rate of commodity production would not influence the overall market demand (decoupling of production rate from global market)